2006
DOI: 10.1152/ajpheart.01362.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particulate matter exposure augments ischemia-reperfusion injury in mice

Abstract: Epidemiological studies have linked ambient particulate matter (PM) levels to an increased incidence of adverse cardiovascular events. Yet little is definitively known about the mechanisms accounting for the cardiovascular events associated with PM exposure. The goal of this study was to determine the effects of ultrafine (<0.1 microm) PM exposure on ischemia-reperfusion (I/R) injury. ICR mice were exposed to 100 microg of PM or vehicle by intratracheal instillation. Twenty-four hours later, mice were anesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 67 publications
(70 reference statements)
5
89
0
1
Order By: Relevance
“…The areas are measured using Scion or NIH imaging software which can be calibrated using a micrometer imaged at the same magnification. These numbers are used to calculate area at risk/left ventricle and infarct size/area at risk 11 . Strain differences can result in variations in body weight and heart size and so care should be taken to normalize these measures to heart weight, body weight, or tibia length for comparative purposes.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The areas are measured using Scion or NIH imaging software which can be calibrated using a micrometer imaged at the same magnification. These numbers are used to calculate area at risk/left ventricle and infarct size/area at risk 11 . Strain differences can result in variations in body weight and heart size and so care should be taken to normalize these measures to heart weight, body weight, or tibia length for comparative purposes.…”
Section: Representative Resultsmentioning
confidence: 99%
“…A solution containing 1% Evan's blue is injected into the aorta. Once the heart is extracted, it is cut transversely into 3 sections of equal thickness, incubated in 1% 2,3,5-triphenyltetrazolium chloride, and imaged for morphometric analyses 11 . For chronic studies, the heart is then immersed in fixative, then processed and embedded according to routine procedures.…”
mentioning
confidence: 99%
“…Relatively high concentrations of intratracheal UFP instillation induced pulmonary inflammation and doubled MI size in mice. 358 Conscious dogs exposed to fine CAP for several days experienced greater ST-segment changes during transient coronary artery occlusion. 378 These studies suggested that particulate-related changes in myocardial blood flow may be responsible, a hypothesis recently supported by experiments in chronically instrumented dogs exposed to fine CAP before transient occlusion of the left anterior descending artery.…”
Section: And Arrhythmiamentioning
confidence: 99%
“…358 Moreover, repeated 10-week-long endotracheal dispersion of UFP carbon black increased atherosclerosis in low-density lipoprotein receptor-knockout mice. 359 This occurred without evidence of systemic translocation of particles into the cardiovascular tissues.…”
Section: Vascular Dysfunction and Atherosclerosismentioning
confidence: 99%
“…PM dikategorikan secara luas menurut diameter aerodinamisnya yaitu fine particle (<2,5µm [PM2.5]) dan ultrafine (<0,1µm [UFP], yang kebanyakan berasal dari gas diesel serta coarse particle (2,5 sampai 10µm [PM10-2,5]), yang berasal dari proses penghancuran dan pengasahan suatu permukaan benda. 3 Mekanisme PM dalam menimbulkan dampak terhadap kesehatan adalah menginduksi efek proinflamasi sel target, seperti sel endothel, makrofag, dan sel epitel melalui pembentukan reactive oxygen species (ROS) dan stres oksidatif. Efek prooksidatif ini dipicu oleh molekul-molekul organik siklus redoks dan metal transisi yang terdapat pada permukaan partikel.…”
Section: Pendahuluanunclassified